Digital Empowerment through Website Development for Early Childhood Education Institutions: A Sustainable Community Engagement Study in Jayapura, Indonesia - Uturestantix; Shanti Shinta Tupamahu; Idham Khaliq (LOSARI DIGITAL, 2026)
Digital transformation has become a strategic necessity for Early Childhood Education institutions (PAUD) in Indonesia. However, many PAUD centers in Eastern Indonesia continue to face capacity constraints in adopting digital technologies, particularly institutional websites. This article examines a sustainability-oriented community service program through website development at PAUD ALFA OMEGA in Jayapura City. The program employed a participatory approach involving needs assessment, website design, training, and continuous mentoring. Data were collected through observation, interviews, documentation, and statistical analysis of website traffic. The findings indicate that within the first month after launch, the website recorded an average of 105 online visits per week. After being indexed by Google’s search engine, the number of parents visiting the school to obtain enrollment forms increased from an average of 10 to 15 per month. The website also continued to be actively managed after the completion of the community service activities, reflecting institutional ownership and sustainability. These results demonstrate that website development integrated with capacity building can function as an effective instrument for institutional empowerment. This study contributes to the development of a sustainable, digitally empowered community service model for early childhood education institutions.